Composition for producing porous membrane, method for producing porous membrane, and porous membrane

JP2025035905APending Publication Date: 2025-03-14TOKYO OHKA KOGYO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023143242
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0018】 本発明によれば、製造される多孔質膜の流量を向上することができる多孔質膜製造用組成物、多孔質膜の製造方法、及び多孔質膜を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035905000001
    Figure 2025035905000001
  • Figure 2025035905000002
    Figure 2025035905000002
  • Figure 2025035905000003
    Figure 2025035905000003
Patent Text Reader

Abstract

To provide a composition for producing a porous membrane which can improve a flow rate of a porous membrane to be produced, a method for producing a porous membrane, and a porous membrane.SOLUTION: A composition for producing a porous membrane contains at least one resin component (A) selected from the group consisting of a polyamide acid, polyimide, a polyamide imide precursor, polyamide imide and polyether sulfone, fine particles (B), and a solvent (S), wherein the solvent (S) contains an organic solvent (S1) and an organic solvent (S2), the organic solvent (S1) is an organic solvent having a boiling point under atmospheric pressure of lower than 200°C, and the organic solvent (S2) is a nitrogen-containing polar solvent having a boiling point under atmospheric pressure of 200°C or higher.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition for producing a porous membrane, a method for producing a porous membrane, and a porous membrane. [Background technology]

[0002] Conventionally, various porous membranes have been used for applications such as filters, which are membranes for separating gases or liquids. In recent years, the application of porous membranes has also progressed for applications as separators for secondary batteries such as lithium batteries.

[0003] For example, a method for producing a porous polyimide film is known in which a varnish in which silica particles are dispersed in a solution of polyamic acid or polyimide is applied onto a substrate, the applied film is heated as necessary to obtain a polyimide film containing silica particles, and then the silica in the polyimide film is dissolved and removed with hydrogen fluoride water to make the polyimide film porous (see Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5605566 Summary of the Invention [Problem to be solved by the invention]

[0005] There is a demand for the above-mentioned porous membrane to have a small pore size. For example, in the manufacture of semiconductors, porous films are used as filters for removing foreign matter contained in cleaning solutions, coating solutions, and the like. As semiconductors become finer, the size of foreign matter that causes defects also becomes smaller. In order to collect small foreign matter, porous films with small pore diameters are required. Note that porous films with small pore diameters can be manufactured by using a porous film manufacturing composition (varnish) that contains fine particles such as silica with a small particle size. However, reducing the pore size of the porous membrane reduces the permeability (liquid permeability and air permeability) of the porous membrane, which causes a problem of a decrease in the flow rate of liquids and gases passing through the porous membrane.

[0006] The present invention has been made in consideration of the above circumstances, and aims to provide a composition for producing a porous membrane, a method for producing a porous membrane, and a porous membrane that can improve the flow rate of the porous membrane produced. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above problems. As a result, they have found that the above problems can be solved by using, as the solvent (S), an organic solvent having a boiling point of less than 200°C under atmospheric pressure and a nitrogen-containing polar solvent having a boiling point of 200°C or higher under atmospheric pressure in a composition for producing a porous membrane, the composition including at least one resin component (A) selected from the group consisting of polyamic acid, polyimide, polyamideimide precursor, polyamideimide, and polyethersulfone, fine particles (B), and a solvent (S), and thus have completed the present invention. Specifically, the present invention provides the following.

[0008] [1] A composition comprising at least one resin component (A) selected from the group consisting of polyamic acid, polyimide, polyamideimide precursor, polyamideimide, and polyethersulfone, fine particles (B), and a solvent (S); The solvent (S) includes an organic solvent (S1) and an organic solvent (S2), The organic solvent (S1) has a boiling point of less than 200° C. under atmospheric pressure, The composition for producing a porous membrane, wherein the organic solvent (S2) is a nitrogen-containing polar solvent having a boiling point of 200° C. or higher under atmospheric pressure.

[0009] [2] The composition for producing a porous membrane according to the above [1], wherein the nitrogen-containing polar solvent as the organic solvent (S2) is at least one selected from the group consisting of nitrogen-containing heterocyclic compounds which may have a substituent and aromatic hydrocarbons substituted with a nitrogen-containing group.

[0010] [3] The composition for producing a porous membrane according to the above [2], wherein the organic solvent (S2) is at least one selected from the group consisting of 1,3-dimethyl-2-imidazolidinone, N-methylpyrrolidone, N-ethyl-2-pyrrolidone, and nitrobenzene.

[0011] [4] The composition for producing a porous membrane according to any one of the above [1] to [3], wherein the organic solvent (S1) is an aliphatic amide solvent.

[0012] [5] The composition for producing a porous membrane according to any one of the above [1] to [4], wherein the organic solvent (S1) is dimethylacetamide.

[0013] [6] The composition for producing a porous membrane according to any one of the above [1] to [5], wherein the ratio of the mass of the organic solvent (S2) to the mass of the solvent (S) is 5 mass% or more and 70 mass% or less.

[0014] [7] The composition for producing a porous membrane according to any one of the above [1] to [6], wherein the content of the organic solvent (S2) is 100 parts by mass or more and 900 parts by mass or less per 100 parts by mass of the resin component (A).

[0015] [8] A composite film formation step of forming a composite film made of the composition for producing a porous film according to any one of the above [1] to [7] on a substrate; a heating step of removing a portion of the solvent (S) from the composite membrane by heating the composite membrane; and a fine particle removing step of removing the fine particles (B) from the composite membrane after the heating step.

[0016] [9] The resin component (A) contains at least one of a polyamic acid and a polyamide-imide precursor, The method for producing a porous membrane according to [8] above, further comprising a calcination step of calcining the composite membrane during the heating step or after the heating step and before the fine particle removal step.

[0017]

[10] A porous membrane comprising at least one resin component selected from the group consisting of polyimide, polyamideimide, and polyethersulfone, and a nitrogen-containing polar solvent having a boiling point of 200° C. or higher under atmospheric pressure, A porous film produced by a production method including: forming a composite film made of the composition for producing a porous film according to any one of the above [1] to [7] on a substrate; heating the composite film to remove a part of the solvent (S) from the composite film; and removing the fine particles (B) from the heated composite film. Effect of the Invention

[0018] According to the present invention, it is possible to provide a composition for producing a porous membrane, a method for producing a porous membrane, and a porous membrane, which are capable of improving the flow rate of the produced porous membrane. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, the embodiments of the present invention will be described in detail, however, the present invention is not limited to the following embodiments and can be practiced with appropriate modifications within the scope of the object of the present invention.

[0020] ≪Composition for producing porous membrane≫ The composition for producing a porous membrane (hereinafter also referred to as "varnish") contains at least one resin component (A) selected from the group consisting of polyamic acid, polyimide, polyamideimide precursor, polyamideimide, and polyethersulfone, fine particles (B), and a solvent (S). The solvent (S) contains an organic solvent (S1) and an organic solvent (S2). The organic solvent (S1) is an organic solvent having a boiling point of less than 200°C under atmospheric pressure. The organic solvent (S2) is a nitrogen-containing polar solvent having a boiling point of 200°C or higher under atmospheric pressure.

[0021] [Resin component (A)] As described above, the composition for producing a porous membrane contains at least one resin component (A) selected from the group consisting of polyamic acid, polyimide, polyamideimide precursor, polyamideimide, and polyethersulfone. The resin component (A) will be described below.

[0022] [Polyamic acid] As the polyamic acid, any product obtained by polymerizing any tetracarboxylic dianhydride and diamine can be used without any particular limitation. The amount of the tetracarboxylic dianhydride and the diamine used is not particularly limited, but it is preferable to use 0.50 to 1.50 moles of the diamine per mole of the tetracarboxylic dianhydride, more preferably 0.60 to 1.30 moles, and particularly preferably 0.70 to 1.20 moles.

[0023] The tetracarboxylic dianhydride can be appropriately selected from tetracarboxylic dianhydrides that have been used as a synthetic raw material for polyamic acid. The tetracarboxylic dianhydride may be an aromatic tetracarboxylic dianhydride or an aliphatic tetracarboxylic dianhydride, but it is preferable to use an aromatic tetracarboxylic dianhydride from the viewpoint of the heat resistance of the resulting polyimide resin. The tetracarboxylic dianhydride may be used alone or in combination of two or more kinds.

[0024] Specific examples of suitable aromatic tetracarboxylic dianhydrides include pyromellitic dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, and 2,2,6,6-biphenyltetracarboxylic dianhydride. Carboxylic acid dianhydrides, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 3,3',4,4'-benzophenone tetraanhydride Carboxylic acid dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, bis(2,3-dicarboxyphenyl)ether dianhydride, 2,2',3,3'-benzophenonetetracarboxylic acid dianhydride, 4,4-(p-phenylenedioxy)diphthalic acid dianhydride, 4,4-(m-phenylenedioxy)diphthalic acid dianhydride, 1,2,5,6-naphthalenetetracarboxylic acid dianhydride, 1,4,5,8-naphthalenetetracarboxylic acid Examples of the aliphatic tetracarboxylic dianhydride include 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, 1,2,7,8-phenanthrenetetracarboxylic dianhydride, 9,9-bisphthalic anhydride fluorene, and 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride. Examples of the aliphatic tetracarboxylic dianhydride include ethylenetetracarboxylic dianhydride, butanetetracarboxylic dianhydride, cyclopentanetetracarboxylic dianhydride, cyclohexanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, and 1,2,3,4-cyclohexanetetracarboxylic dianhydride. Among these, 3,3',4,4'-biphenyltetracarboxylic dianhydride and pyromellitic dianhydride are preferred in terms of price, availability, and the like.These tetracarboxylic dianhydrides may be used alone or in combination of two or more.

[0025] The diamine can be appropriately selected from diamines that have been used as a synthetic raw material for polyamic acid. The diamine can be an aromatic diamine or an aliphatic diamine, but from the viewpoint of the heat resistance of the resulting polyimide resin, an aromatic diamine is preferable. These diamines can be used alone or in combination of two or more.

[0026] Examples of aromatic diamines include diamino compounds having one or about 2 to 10 phenyl groups bonded thereto, specifically phenylenediamine and its derivatives, diaminobiphenyl compounds and their derivatives, diaminodiphenyl compounds and their derivatives, diaminotriphenyl compounds and their derivatives, diaminonaphthalene and its derivatives, aminophenylaminoindan and its derivatives, diaminotetraphenyl compounds and their derivatives, diaminohexaphenyl compounds and their derivatives, and cardo-type fluorenediamine derivatives.

[0027] The phenylenediamines include m-phenylenediamine and p-phenylenediamine, and the phenylenediamine derivatives include diamines having alkyl groups such as methyl groups and ethyl groups bonded thereto, for example, 2,4-diaminotoluene and 2,4-triphenylenediamine.

[0028] In diaminobiphenyl compounds, two aminophenyl groups are bonded together, such as 4,4'-diaminobiphenyl and 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl.

[0029] A diaminodiphenyl compound is a compound in which two aminophenyl groups are bonded to each other via another group. The bond is an ether bond, a sulfonyl bond, a thioether bond, a bond by an alkylene or its derivative group, an imino bond, an azo bond, a phosphine oxide bond, an amide bond, a ureylene bond, or the like. The number of carbon atoms in the alkylene bond is about 1 to 6. The derivative group of the alkylene group is an alkylene group substituted with one or more halogen atoms, or the like.

[0030] Examples of the diaminodiphenyl compound include 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl methane, 3,4'-diaminodiphenyl methane, 4,4'-diaminodiphenyl methane, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl ketone, 3,4'-diaminodiphenyl ketone, 2,2-bis(p-aminophenyl)propane, 2,2'-bis(p-aminophenyl)hexafluoropropane, 4-methyl-2,4-bis(p-aminophenyl)-1-pentene, 4-methyl-2,4-bis(p-aminophenyl) p-aminophenyl)-2-pentene, iminodianiline, 4-methyl-2,4-bis(p-aminophenyl)pentane, bis(p-aminophenyl)phosphine oxide, 4,4'-diaminoazobenzene, 4,4'-diaminodiphenylurea, 4,4'-diaminodiphenylamide, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, and the like.

[0031] Among these, p-phenylenediamine, m-phenylenediamine, 2,4-diaminotoluene, and 4,4'-diaminodiphenyl ether are preferred in view of cost, availability, and the like.

[0032] A diaminotriphenyl compound is a compound in which two aminophenyl groups and one phenylene group are bonded via other groups. The other groups are selected from the same groups as those of the diaminodiphenyl compound. Examples of the diaminotriphenyl compound include 1,3-bis(m-aminophenoxy)benzene, 1,3-bis(p-aminophenoxy)benzene, and 1,4-bis(p-aminophenoxy)benzene.

[0033] Examples of diaminonaphthalenes include 1,5-diaminonaphthalene and 2,6-diaminonaphthalene.

[0034] Examples of aminophenylaminoindanes include 5 or 6-amino-1-(p-aminophenyl)-1,3,3-trimethylindan.

[0035] Examples of diaminotetraphenyl compounds include 4,4'-bis(p-aminophenoxy)biphenyl, 2,2'-bis[p-(p'-aminophenoxy)phenyl]propane, 2,2'-bis[p-(p'-aminophenoxy)biphenyl]propane, and 2,2'-bis[p-(m-aminophenoxy)phenyl]benzophenone.

[0036] Examples of the cardo-type fluorenediamine derivatives include 9,9-bisanilinefluorene.

[0037] The number of carbon atoms of the aliphatic diamine is, for example, about 2 to 15. Specific examples of the aliphatic diamine include pentamethylene diamine, hexamethylene diamine, and heptamethylene diamine.

[0038] The diamine may be a compound in which a hydrogen atom of the diamine is substituted with at least one substituent selected from the group consisting of halogen atoms, methyl groups, methoxy groups, cyano groups, phenyl groups, and the like.

[0039] There is no particular limitation on the means for producing the polyamic acid, and for example, a known method such as a method of reacting an acid and a diamine component in a solvent can be used.

[0040] The reaction between the tetracarboxylic dianhydride and the diamine is usually carried out in a solvent. The solvent used in the reaction between the tetracarboxylic dianhydride and the diamine is not particularly limited as long as it can dissolve the tetracarboxylic dianhydride and the diamine and does not react with the tetracarboxylic dianhydride and the diamine. The solvent may be used alone or in combination of two or more.

[0041] Examples of the solvent used in the reaction between the tetracarboxylic dianhydride and the diamine include nitrogen-containing polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dimethylformamide, N,N-diethylformamide, N-methylcaprolactam, and N,N,N',N'-tetramethylurea; lactone-based polar solvents such as β-propiolactone, γ-butyrolactone, γ-valerolactone, δ-valerolactone, γ-caprolactone, and ε-caprolactone; dimethyl sulfoxide; acetonitrile; fatty acid esters such as ethyl lactate and butyl lactate; ethers such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, dioxane, tetrahydrofuran, methyl cellosolve acetate, and ethyl cellosolve acetate; and phenol-based solvents such as cresols and xylene-based mixed solvents. These solvents may be used alone or in combination of two or more. There is no particular restriction on the amount of the solvent used, but it is desirable that the content of the produced polyamic acid be 5 to 50 mass %.

[0042] As the solvent used in the reaction between the tetracarboxylic dianhydride and the diamine, it is preferable to use the solvent (S) contained in the varnish, specifically, the organic solvent (S1) or the organic solvent (S2) described in detail later. When the organic solvent (S1) contained in the varnish is used as the solvent used in the reaction between the tetracarboxylic dianhydride and the diamine, for example, by adding the organic solvent (S2) after the reaction between the tetracarboxylic dianhydride and the diamine, a varnish containing the organic solvent (S1) and the organic solvent (S2) can be easily produced. In addition, when the organic solvent (S1) or the organic solvent (S2) contained in the varnish is not used as the solvent for the reaction between the tetracarboxylic dianhydride and the diamine, the solvent may be replaced with the organic solvent (S1) or the organic solvent (S2) after the reaction.

[0043] The polymerization temperature is generally −10 to 120° C., and preferably 5 to 30° C. The polymerization time varies depending on the composition of the raw materials used, but is usually 3 to 24 hours. The polyamic acid may be used alone or in combination of two or more kinds.

[0044] [Polyimide] The structure and molecular weight of the polyimide are not limited, and any known polyimide can be used. The polyimide may have a condensable functional group such as a carboxyl group or a functional group that promotes a crosslinking reaction during baking in the side chain. In addition, a soluble polyimide that can be dissolved in the organic solvent (S1) or organic solvent (S2) contained in the varnish is preferable.

[0045] In order to make the polyimide soluble in the organic solvent (S1) or the organic solvent (S2), a monomer for introducing a flexible bent structure into the main chain is used, for example, an aliphatic diamine such as ethylenediamine, hexamethylenediamine, 1,4-diaminocyclohexane, 1,3-diaminocyclohexane, or 4,4'-diaminodicyclohexylmethane; 2-methyl-1,4-phenylenediamine, o-tolidine, m-tolidine, 3,3'-dimethoxybenzidine, 4,4'- It is effective to use aromatic diamines such as diaminobenzanilide; polyoxyalkylene diamines such as polyoxyethylene diamine, polyoxypropylene diamine, and polyoxybutylene diamine; polysiloxane diamine; 2,3,3',4'-oxydiphthalic anhydride, 3,4,3',4'-oxydiphthalic anhydride, 2,2-bis(4-hydroxyphenyl)propane dibenzoate-3,3',4,4'-tetracarboxylic dianhydride, etc. It is also effective to use a monomer having a functional group that improves solubility in a solvent, for example, a fluorinated diamine such as 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl or 2-trifluoromethyl-1,4-phenylenediamine. Furthermore, in addition to the monomer for improving the solubility of the polyimide, the same monomer as the monomer described in the polyamic acid column above can also be used in combination within a range that does not inhibit solubility. The polyimide and the monomer thereof may each be used alone or in combination of two or more kinds.

[0046] There is no particular limitation on the means for producing polyimide. For example, known methods such as chemical imidization or thermal imidization of polyamic acid can be used. Examples of such polyimides include aliphatic polyimides (all aliphatic polyimides) and aromatic polyimides, and aromatic polyimides are preferred. Examples of aromatic polyimides include those obtained by subjecting polyamic acid having a repeating unit represented by formula (1) to a ring-closing reaction by thermal or chemical means, or polyimides having a repeating unit represented by formula (2). In the formula, Ar represents an aryl group. These polyimides are then preferably dissolved in the organic solvent (S1) or organic solvent (S2) to be used. [ka] [ka]

[0047] [Polyamide-imide and polyamide-imide precursors] The polyamideimide is not limited in structure or molecular weight, and known polyamideimides can be used. The polyamideimide may have a condensable functional group such as a carboxyl group or a functional group that promotes a crosslinking reaction during baking in the side chain. In addition, soluble polyamideimides that can be dissolved in the organic solvent (S1) or organic solvent (S2) contained in the varnish are preferred.

[0048] Polyamideimides that can be used are generally, without any particular limitations, and include (i) resins obtained by reacting an acid having a carboxyl group and an acid anhydride group in one molecule, such as trimellitic anhydride, with a diisocyanate, and (ii) resins obtained by imidizing a precursor polymer (polyamideimide precursor) obtained by reacting a reactive derivative of the above acid, such as trimellitic anhydride chloride, with a diamine.

[0049] Examples of the above acid or reactive derivatives thereof include trimellitic anhydride, trimellitic anhydride halides such as trimellitic anhydride chloride, and trimellitic anhydride esters.

[0050] The optional diamine may be any of the diamines exemplified in the above description of polyamic acid, and may also be a diaminopyridine compound.

[0051] The optional diisocyanate is not particularly limited, and examples thereof include diisocyanate compounds corresponding to the optional diamines. Specific examples thereof include metaphenylene diisocyanate, p-phenylene diisocyanate, o-tolidine diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, 4,4'-oxybis(phenylisocyanate), 4,4'-diisocyanatodiphenylmethane, bis[4-(4-isocyanatophenoxy)phenyl]sulfone, 2,2'- ... anatophenoxy)phenyl]propane, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 3,3'-dimethyldiphenyl-4,4'-diisocyanate, 3,3'-diethyldiphenyl-4,4'-diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, m-xylene diisocyanate, p-xylene diisocyanate, naphthalene diisocyanate, and the like.

[0052] In addition to the above, compounds described as general formulas in JP-A-63-283705 and JP-A-2-198619 can also be used as raw material monomers for polyamideimide. The imidization in the above method (ii) can be either thermal imidization or chemical imidization. For chemical imidization, a composite film (unbaked composite film) formed using a varnish containing a polyamideimide precursor or the like can be immersed in acetic anhydride or a mixed solvent of acetic anhydride and isoquinoline. The polyamideimide precursor can also be called a polyimide precursor from the viewpoint of a precursor before imidization.

[0053] The polyamideimide contained in the varnish may be the above-mentioned (1) polymer obtained by reacting an acid such as trimellitic anhydride with a diisocyanate, or (2) a polymer obtained by imidizing a precursor polymer obtained by reacting a reactive derivative of the above acid such as trimellitic anhydride chloride with a diamine, etc. In this specification and claims, "polyamideimide precursor" means a polymer (precursor polymer) before imidization. Each of the polyamideimide and the polyamideimide precursor may be used alone or in combination of two or more. In addition, for the polyamideimide, each of the above-mentioned polymers, raw material monomers, and oligomers may be used alone or in combination of two or more.

[0054] [Polyethersulfone] The polyethersulfone is not particularly limited as long as it is soluble in the organic solvent (S1) or the organic solvent (S2) used in the varnish. The polyethersulfone can be appropriately selected depending on the application of the porous membrane to be produced, and may be hydrophilic or hydrophobic. In addition, it may be an aliphatic polyethersulfone or an aromatic polyethersulfone. The mass average molecular weight is, for example, 5000 to 1,000,000, and preferably 10,000 to 300,000.

[0055] [Fine particles (B)] The material of the fine particles (B) is not particularly limited, and any known material can be used as long as it is insoluble in the solvent (S) contained in the varnish and can be subsequently removed from the composite film (resin-fine particle composite film). For example, inorganic materials include metal oxides such as silica (silicon dioxide), titanium oxide, and alumina (Al2O3), while organic materials include organic polymer particles such as high molecular weight olefins (polypropylene, polyethylene, etc.), polystyrene, epoxy resin, cellulose, polyvinyl alcohol, polyvinyl butyral, polyester, and polyether.

[0056] Specifically, the fine particles (B) include, for example, colloidal silica. Among them, it is preferable to select monodispersed spherical silica particles because they can form uniform pores.

[0057] Moreover, it is preferable that the fine particles (B) have a high sphericity and a small particle size distribution index. The fine particles (B) that satisfy these conditions have excellent dispersibility in the varnish and can be used in a state where they do not aggregate with each other. The average particle size of the fine particles (B) used is, for example, preferably 10 nm or more and 500 nm or less, more preferably 50 nm or more and 300 nm or less, and even more preferably 70 nm or more and 150 nm or less. In this specification, the average particle size of the fine particles (B) is D50, which means the particle size at an integrated value of 50% in the volume-based particle size distribution determined by a laser diffraction / scattering method. The size of the pores formed in the porous film and originating from the fine particles (B) is the same as or close to the average particle size of the fine particles (B). The fine particles (B) may be used alone or in combination of two or more kinds.

[0058] Solvent The solvent (S) includes an organic solvent (S1) and an organic solvent (S2). The organic solvent (S1) is an organic solvent having a boiling point (hereinafter also simply referred to as "boiling point") of less than 200°C under atmospheric pressure. The organic solvent (S2) is a nitrogen-containing polar solvent having a boiling point of 200°C or higher under atmospheric pressure.

[0059] The varnish contains, as the solvent (S), an organic solvent (S1) having a boiling point of less than 200°C at atmospheric pressure and an organic solvent (S2) being a nitrogen-containing polar solvent having a boiling point of 200°C or higher at atmospheric pressure, and thereby the flow rate of the porous membrane produced can be improved, as shown in the examples described later. This is believed to be due to the following reasons. The nitrogen-containing polar solvent interacts (by hydrogen bonding, etc.) with the resin component (A) such as polyamic acid, and enhances the orientation of the resin component (A). When a nitrogen-containing polar solvent (organic solvent (S2)) having a high boiling point of 200°C or higher at atmospheric pressure is used in addition to an organic solvent (organic solvent (S1)) having a boiling point of less than 200°C at atmospheric pressure, the nitrogen-containing polar solvent (organic solvent (S2)) remains in the film upon heating and the resin component (A) forms a highly oriented structure, thereby improving the film strength. When the membrane strength is improved, pore collapse can be suppressed. For example, when the resin component (A) contains a polyamic acid or a polyamideimide precursor, when the polyamic acid is converted to a polyimide or when the polyamideimide precursor is converted to a polyamideimide, residual stress occurs due to volume shrinkage, which tends to cause pore collapse. However, when the membrane strength is high, such pore collapse can be suppressed. This prevents the flow rate of the fluid (liquid or gas) passing through the porous membrane from decreasing due to pore collapse, and improves (increases) the flow rate. In other words, the flow rate of the fluid passing through the porous membrane can be increased. For example, when the porous membrane is used as a filter, the processing flow rate (filtration flow rate) can be improved.

[0060] Here, by using a varnish containing fine particles with a small particle size, a porous membrane with a small pore size can be produced. On the other hand, reducing the pore size of a porous membrane reduces the permeability (liquid permeability and air permeability) of the porous membrane, and reduces the flow rate of liquid or gas passing through the porous membrane. For example, in filter applications, this causes a problem of a reduced processing flow rate (filtration flow rate). However, by using the above-mentioned varnish, the flow rate can be improved, so that both the pore size and the flow rate can be reduced. Therefore, a porous membrane having a small pore size and a large flow rate can be produced.

[0061] On the other hand, when a varnish containing only the organic solvent (S1) is used as the solvent (S), or when the varnish contains the organic solvent (S1) and an organic solvent whose boiling point at atmospheric pressure is 200°C or higher but which is not a nitrogen-containing polar solvent, the flow rate is low and the film strength is also low.

[0062] The boiling point of the organic solvent (S1) may be less than 200° C., but is preferably 180° C. or less, and more preferably 170° C. or less. The boiling point of the organic solvent (S1) is preferably 100° C. or more, and more preferably 120° C. or more. The organic solvent (S1) may be an aliphatic amide solvent. The organic solvent (S1) may be an aliphatic amide solvent such as dimethylacetamide (boiling point: 165° C.). The organic solvent (S1) may be one type or two or more types.

[0063] The boiling point of the organic solvent (S2) may be 200° C. or higher, may be 210° C. or higher, or may be 220° C. or higher. Examples of the nitrogen-containing polar solvent as the organic solvent (S2) include nitrogen-containing heterocyclic compounds which may have a substituent, and aromatic hydrocarbons substituted with a nitrogen-containing group. Examples of the nitrogen-containing heterocyclic compound which may have a substituent as the organic solvent (S2) include 1,3-dimethyl-2-imidazolidinone (boiling point 220° C.), N-methylpyrrolidone (boiling point 202° C.), and N-ethyl-2-pyrrolidone (boiling point 218° C.). An example of the nitrogen-containing group is a nitro group. An example of the aromatic hydrocarbon substituted with a nitrogen-containing group as the organic solvent (S2) is nitrobenzene (210° C.). The organic solvent (S2) may be one type or two or more types.

[0064] In addition, in order to form a porous membrane, the solvent (S), the organic solvent (S1) and the organic solvent (S2) are solvents that can dissolve the resin component (A) contained in the varnish, which is composed of polyamic acid, polyimide, polyamideimide precursor, polyamideimide and / or polyethersulfone, but do not dissolve the microparticles (B).

[0065] The ratio of the mass of the organic solvent (S2) to the mass of the solvent (S) is preferably 5 mass% or more and 70 mass% or less, more preferably 10 mass% or more and 60 mass% or less, and even more preferably 20 mass% or more and 50 mass% or less. In addition, the content of the organic solvent (S2) in the varnish is preferably 100 parts by mass or more and 900 parts by mass or less, more preferably 200 parts by mass or more and 800 parts by mass or less, and even more preferably 300 parts by mass or more and 700 parts by mass or less, per 100 parts by mass of the resin component (A).

[0066] [Dispersant] A dispersant may be added together with the fine particles (B) in order to uniformly disperse the fine particles (B) in the varnish. By adding a dispersant, the fine particles (B) can be mixed more uniformly in the varnish, and furthermore, the fine particles (B) can be uniformly distributed in the film formed from the varnish. As a result, dense openings can be provided on the surface of the finally obtained porous film, and the front and back surfaces can be efficiently connected, improving the air permeability of the porous film. Furthermore, by adding a dispersant, the drying property of the varnish is easily improved, and the peelability of the formed unfired composite film from the substrate, etc. is easily improved.

[0067] The dispersant is not particularly limited, and known dispersants can be used. For example, anionic surfactants such as coconut fatty acid salts, castor sulfate oil salts, lauryl sulfate salts, polyoxyalkylene allyl phenyl ether sulfate salts, alkylbenzene sulfonic acid, alkylbenzene sulfonate salts, alkyl diphenyl ether disulfonate salts, alkyl naphthalene sulfonate salts, dialkyl sulfosuccinate salts, isopropyl phosphate, polyoxyethylene alkyl ether phosphate salts, and polyoxyethylene allyl phenyl ether phosphate salts; cationic surfactants such as oleylamine acetate, lauryl pyridinium chloride, cetyl pyridinium chloride, lauryl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, behenyl trimethyl ammonium chloride, and didecyl dimethyl ammonium chloride; amphoteric surfactants such as coconut alkyl dimethyl amine oxide, fatty acid amidopropyl dimethyl amine oxide, alkyl polyaminoethyl glycine hydrochloride, amido betaine type surfactants, alanine type surfactants, and lauryl imino dipropionic acid; polyoxy Nonionic surfactants of polyoxyalkylene primary alkyl ethers or polyoxyalkylene secondary alkyl ethers, such as ethylene octyl ether, polyoxyethylene decyl ether, polyoxyethylene lauryl ether, polyoxyethylene laurylamine, polyoxyethylene oleylamine, polyoxyethylene polystyrylphenyl ether, and polyoxyalkylene polystyrylphenyl ether; other polyoxyalkylene-based nonionic surfactants, such as polyoxyethylene dilaurate, polyoxyethylene laurate, polyoxyethylenated castor oil, polyoxyethylenated hydrogenated castor oil, sorbitan laurate, polyoxyethylene sorbitan laurate, and fatty acid diethanolamide; fatty acid alkyl esters, such as octyl stearate and trimethylolpropane tridecanoate; and polyether polyols, such as polyoxyalkylene butyl ether, polyoxyalkylene oleyl ether, and trimethylolpropane tris(polyoxyalkylene)ether, but are not limited to these.The above dispersants can also be used in combination of two or more.

[0068] In the varnish, the content of the dispersant is, for example, from the viewpoint of film-forming properties, preferably from 0.01% by mass to 5% by mass, more preferably from 0.05% by mass to 1% by mass, and even more preferably from 0.1% by mass to 0.5% by mass, relative to the mass of the microparticles (B).

[0069] The method for producing the composition for producing a porous membrane (varnish) is not particularly limited. The varnish is typically produced by a microparticle dispersion preparation step of dispersing microparticles (B) in a solvent, a step of preparing a resin solution containing resin component (A), and a kneading step of combining and kneading the microparticle dispersion and the resin solution to adjust the concentration.

[0070] The varnish preferably has a viscosity of 0.1 to 3 Pa·s at 25° C. and a solid content of 10% by mass or more and 50% by mass or less. The varnish is produced by kneading for preferably 2 minutes to 10 hours, more preferably 2 minutes to 60 minutes. The viscosity of the varnish is measured by an E-type viscometer. For kneading the varnish, a planetary mixer, a bead mill, or the like can be used. In addition, in the kneading process, the cross-sectional area is 1960 μm 2 More than 785000μm 2 A dispersion device having the following flow path may be used to pass a mixed liquid (slurry) containing a microparticle dispersion and a resin solution pressurized to 50 MPa or more through the flow path to perform a dispersion process. Examples of a method for performing a dispersion process by passing the mixture through such a flow path include the method described in JP 2020-104105 A.

[0071] <Method for manufacturing porous membrane> The method for producing a porous film includes a composite film formation step of forming a composite film made of the above-mentioned composition for producing a porous film on a substrate, a heating step of removing a portion of the solvent (S) from the composite film by heating the composite film, and a particle removal step of removing the particles (B) from the composite film after the heating step. In addition, the method for producing a porous membrane may include a baking step in which the resin component (A) contains at least one of a polyamic acid and a polyamideimide precursor, and the composite membrane is baked during the heating step or after the heating step and before the fine particle removal step.

[0072] [Composite membrane formation process (production of unsintered composite membrane)] In the composite film forming step, a composite film made of the above-mentioned porous film production composition (varnish) is formed on a substrate. The composite film (hereinafter also referred to as "unsintered composite film") may be formed (deposited) directly on a substrate, or may be formed (deposited) on an underlayer film different from the unsintered composite film. In addition, after forming an unsintered composite film using the above-mentioned varnish (composition for producing a porous film), an upper layer film different from the unsintered composite film may be further formed on the upper layer. In this application, the method of providing an underlayer film on a substrate and the method of forming an unsintered composite film using the above-mentioned varnish and then forming an upper layer film different from the unsintered composite film on the upper layer are also included in the method of forming an unsintered composite film on a substrate. However, when the resin component (A) contained in the above-mentioned varnish is a polyamic acid or a polyamideimide precursor and a material that does not require a sintering process is used for the upper layer film, an upper layer film may be formed on the resin-particle composite film after sintering. The composite film (unfired composite film) made of the above-mentioned varnish is preferably formed as a single layer film on a substrate. Examples of the substrate include a PET film, a SUS substrate, and a glass substrate.

[0073] The lower layer (or upper layer) film may be, for example, a lower layer (or upper layer) unsintered composite film formed using a lower layer (or upper layer) film varnish containing a resin component consisting of polyamic acid, polyimide, polyamideimide precursor, polyamideimide and / or polyethersulfone, fine particles, and a solvent, and the content of the fine particles is more than 40 volume % and 81 volume % or less with respect to the total of the resin component and the fine particles. The lower layer (or upper layer) unsintered composite film may be formed on a substrate. When the content of the fine particles is more than 40 volume %, the particles are uniformly dispersed, and when the content of the fine particles is 81 volume % or less, the particles are dispersed without agglomeration, so that holes can be formed uniformly in the porous film. In addition, if the content of the fine particles is within the above range, when the lower layer (or upper layer) unsintered composite film is formed on a substrate, even if a release layer is not provided in advance on the substrate, the release property after film formation is easily ensured.

[0074] The fine particles used in the varnish for the lower (or upper) layer film may be the same as or different from the fine particles (B) used in the varnish described above. In order to make the pores in the unsintered lower (or upper) layer composite film more dense, it is preferable that the fine particles used in the varnish for the lower (or upper) layer film have a particle size distribution index smaller than or equal to that of the fine particles (B) used in the varnish described above. Alternatively, it is preferable that the fine particles used in the varnish for the lower (or upper) layer film have a sphericity smaller than or equal to that of the fine particles (B) used in the varnish described above.

[0075] In addition, the average particle size of the fine particles used in the varnish for the lower layer (or upper layer) film may be the same as or different from the average particle size of the fine particles (B) of the varnish described above. The average particle size may be appropriately set within the range of 10 nm to 5000 nm depending on the application. When using a varnish for the lower layer (or upper layer) film, it is preferable to use the above-mentioned varnish as the upper layer in combination with a varnish for the lower layer film having a different average particle size or particle size distribution index of the fine particles.

[0076] The content of the fine particles in the varnish for forming the lower layer (or upper layer) film may be greater or less than that of the above-mentioned varnish. Suitable examples of the components such as the resin component, fine particles, and solvent contained in the varnish for forming the lower layer (or upper layer) film are the same as those in the above-mentioned varnish. The varnish for forming the lower layer (or upper layer) film can be prepared by the same method as that for the above-mentioned varnish. The lower layer unsintered composite film can be formed, for example, by applying the above-mentioned varnish for forming the lower layer film onto a substrate and drying at 0 to 100°C under normal pressure or in vacuum, preferably at 10 to 100°C under normal pressure. The film formation conditions for the upper layer unsintered composite film are also similar.

[0077] Examples of the lower (or upper) layer include a lower layer made of a fiber material such as a cellulose resin or a nonwoven fabric (e.g., a polyimide nonwoven fabric, etc., with a fiber diameter of, for example, about 50 nm to about 3000 nm), and a polyimide film.

[0078] Further, the process enters into a firing step in which the unsintered composite film or the laminated film of the unsintered composite film and the lower (or upper) film is fired to obtain a polyimide-fine particle composite film. When the unsintered composite film or the lower unsintered composite film is formed on a substrate, it may be fired as it is, or the unsintered composite film or the laminated film of the unsintered composite film and the lower unsintered composite film may be peeled off from the substrate before the firing step.

[0079] In addition, when the lower layer (or upper layer) film in the laminated film is a lower layer (or upper layer) unsintered composite film formed using a varnish for the lower layer (or upper layer) film, and the composition of the varnish for the lower layer (or upper layer) film is the same as the composition of the varnish described above, the laminated film of the composite film (unsintered composite film) and the lower layer (or upper layer) film is essentially one layer (single layer), but is referred to as a laminated film in this specification.

[0080] When peeling off a composite film (unfired composite film) or a laminated film of an unfired composite film and a lower (or upper) unfired composite film from a substrate, a substrate on which a release layer has been provided in advance can be used to further enhance the peelability of the film. When a release layer is provided in advance on a substrate, a release agent is applied to the substrate and dried or baked before applying the varnish. The release agent used here can be any known release agent such as an alkyl ammonium phosphate salt, a fluorine-based or a silicon-based release agent, without any particular restrictions. When peeling off the unfired composite film from a substrate, a small amount of release agent remains on the peeled surface of the unfired composite film, which may cause discoloration during firing or adversely affect electrical properties, so it is preferable to remove it as much as possible. In order to remove the release agent, a cleaning process may be introduced in which the unfired composite film peeled off from the substrate or the laminated film of the unfired composite film and the lower unfired composite film is washed with an organic solvent.

[0081] On the other hand, when the substrate is used as it is without providing a release layer for forming the unfired composite film or the lower unfired composite film, the above-mentioned release layer forming step and the above-mentioned cleaning step can be omitted. In addition, in the production of the unfired composite film, a step of immersion in a solvent containing water, a pressing step, and a drying step after the immersion step may each be provided as an optional step before the firing step described below.

[0082] [Heating process] In the heating step, the composite film (unsintered composite film) is heated to remove a part of the solvent (S) from the composite film, i.e., the heating step is a drying step. In the heating step, the composite membrane is heated at a temperature at which at least a portion of the organic solvent (S1) is removed from the composite membrane under conditions in which a portion of the organic solvent (S2) remains in the composite membrane. The heating temperature is, for example, preferably from 40° C. to 170° C., more preferably from 60° C. to 145° C. The heating step may be carried out under normal pressure, reduced pressure, or vacuum.

[0083] By the organic solvent (S2) remaining in the composite membrane during heating, the organic solvent (S2) interacts with the resin component (A) and improves the orientation of the resin component (A). This improves the strength of the composite membrane after the heating process (drying process), suppresses the decrease in the flow rate of the fluid (liquid or gas) passing through the porous membrane due to pore collapse, and improves (increases) the flow rate.

[0084] [Baking process (production of resin-particle composite film)] The calcination step is a step of calcining the composite film during or after the heating step and before the particulate removal step. The firing step may be carried out after the heating step (drying step), or may be carried out during the heating step; that is, the heating in the firing step may also serve as the heating (drying) in the heating step.

[0085] When the resin component (A) contained in the varnish contains a polyamic acid and / or a polyamideimide precursor, a composite film (unsintered composite film) consisting of a resin made of polyimide and / or polyamideimide and fine particles (B) is formed by subjecting the composite film (unsintered composite film) to a baking process. When the resin component (A) contains a polyamic acid or a polyamideimide precursor, when the polyamic acid is converted to a polyimide or when the polyamideimide precursor is converted to a polyamideimide in the baking process, residual stress occurs due to volume shrinkage, which causes pore collapse and the flow rate of the formed porous film is likely to decrease. However, when the above-mentioned varnish is used, the strength of the baked film is increased, so that such pore collapse can be suppressed and the flow rate of the porous film can be improved. When the resin component (A) contained in the varnish is a polyimide, a polyamideimide or a polyethersulfone, the baking step may be included, but the baking step may be omitted.

[0086] In the composite film forming step, when the unsintered composite film is formed on an underlayer film different from the unsintered composite film, the underlayer film is also fired together with the unsintered composite film in the firing step.

[0087] The firing temperature in the firing step varies depending on the structures of the composite film and the underlayer film and the presence or absence of a condensing agent, but is preferably from 120° C. to 450° C., more preferably from 150° C. to 420° C. When an organic material is used for the fine particles (B), the firing temperature must be set lower than the thermal decomposition temperature. When the resin component (A) contained in the varnish is a polyamic acid, it is preferable to complete the imidization in the baking step.

[0088] The firing conditions may be, for example, a method in which the temperature is raised from room temperature to 400° C. or lower over 3 hours, followed by holding at 400° C. for 20 minutes, or a stepwise drying-thermal imidization method in which the temperature is raised from room temperature to 400° C. in increments of 50° C. (each step is held for 20 minutes), and finally held at 400° C. for 20 minutes. When an unfired composite film is formed on a substrate and then peeled off from the substrate, a method in which the ends of the unfired composite film are fixed to a SUS mold or the like to prevent deformation can be used.

[0089] The thickness of the completed resin-particle composite membrane can be determined by, for example, measuring the thickness at multiple locations with a micrometer and averaging the measured thickness. The preferred average membrane thickness varies depending on the use of the porous membrane, but for example, when used as a separator, it is preferably 5 μm to 500 μm, more preferably 10 μm to 100 μm, and even more preferably 15 μm to 30 μm. When used as a filter, it is preferably 5 μm to 500 μm, more preferably 10 μm to 300 μm, and even more preferably 20 μm to 150 μm.

[0090] [Particle removal process (making the resin-particle composite membrane porous)] In the particle removal step, the particles (B) are removed from the composite film after the heating step (if a baking step is performed, the composite film (resin-particle composite film) after the baking step). By selecting an appropriate method for removing the particles (B), the porous film can be produced with good reproducibility.

[0091] When silica is used as the material of the fine particles (B), for example, the resin-fine particle composite film can be treated with low-concentration hydrogen fluoride water or the like to dissolve and remove the silica.

[0092] An organic material can also be selected as the material of the fine particles (B). The organic material can be used without any particular limitation as long as it decomposes at a lower temperature than the resin contained in the resin-fine particle composite film. For example, resin fine particles made of linear polymers or known depolymerizable polymers can be mentioned. In a normal linear polymer, the molecular chain of the polymer is randomly cut during thermal decomposition, and in a depolymerizable polymer, the polymer is decomposed into monomers during thermal decomposition. In either case, it disappears from the porous film by decomposing into low molecular weight substances or CO2. The decomposition temperature of the resin fine particles used is preferably 230°C or higher and 320°C or lower.

[0093] The overall thickness of the porous membrane is not particularly limited, but for example, when used as a separator, it is preferably 5 μm to 500 μm, more preferably 10 μm to 100 μm, and even more preferably 15 μm to 30 μm. When used as a filter, it is preferably 5 μm to 500 μm, more preferably 10 μm to 300 μm, and even more preferably 20 μm to 150 μm. The above-mentioned thickness can be obtained by measuring the thickness at multiple points with, for example, a micrometer, and averaging them, in the same manner as when measuring the resin-particle composite membrane.

[0094] In the case where the porous membrane is formed from two or more kinds of compositions for producing a porous membrane, the ratio of the thickness direction of the regions formed by each composition for producing a porous membrane may be appropriately set according to the use of the porous membrane. In the case of a porous membrane having two regions, a layer (I) made of a composition for producing a porous membrane and a layer (II) made of another composition for producing a porous membrane, the ratio of the thickness direction of each region ((I):(II)) may be, for example, 1:99 to 99:1, and preferably 5:95 to 95:5. The thickness of each layer may be calculated by averaging the observation of multiple points on the cross section of the porous membrane using a scanning electron microscope (SEM) or the like.

[0095] [Resin removal process] The method for producing a porous membrane may include a resin removal step of removing at least a part of the resin portion of the resin-particle composite membrane before the microparticle removal step, or removing at least a part of the porous membrane after the microparticle removal step. By removing at least a part of the resin portion of the resin-particle composite membrane or at least a part of the porous membrane, it is possible to improve the porosity of the porous membrane in the final product, compared to the case where the resin portion is not removed.

[0096] The step of removing at least a part of the resin portion or the step of removing at least a part of the porous film can be carried out by a common chemical etching method or a physical removal method, or a combination of these methods.

[0097] Examples of chemical etching methods include treatment with a chemical etching solution such as an inorganic alkaline solution or an organic alkaline solution. Inorganic alkaline solutions are preferred. Examples of inorganic alkaline solutions include hydrazine solutions containing hydrazine hydrate and ethylenediamine, solutions of alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, sodium carbonate, sodium silicate, and sodium metasilicate, ammonia solutions, and etching solutions mainly composed of alkali hydroxide, hydrazine, and 1,3-dimethyl-2-imidazolidinone. Examples of organic alkaline solutions include alkaline solutions of primary amines such as ethylamine and n-propylamine; secondary amines such as diethylamine and di-n-butylamine; tertiary amines such as triethylamine and methyldiethylamine; alcohol amines such as dimethylethanolamine and triethanolamine; quaternary ammonium salts such as tetramethylammonium hydroxide and tetraethylammonium hydroxide; and cyclic amines such as pyrrole and piheridine.

[0098] The solvent for each of the above solutions may be selected from pure water and alcohols. Also, a solution containing an appropriate amount of a surfactant may be used. The alkali concentration is, for example, 0.01 to 20% by mass.

[0099] As a physical method, for example, dry etching using plasma (oxygen, argon, etc.) or corona discharge, or a surface treatment method in which an abrasive (e.g., alumina (hardness 9)) is dispersed in a liquid and irradiated onto the surface of the film at a speed of 30 to 100 m / s can be used.

[0100] The above-mentioned method is preferable because it can be applied to the resin removal step either before or after the fine particle removal step.

[0101] On the other hand, as a physical method applicable only to the resin removal process performed after the fine particle removal process, a method can be adopted in which the target surface is pressed against a mount film (e.g., a polyester film such as a PET film) wetted with a liquid, and then the porous membrane is peeled off from the mount film, either without drying or after drying. Due to the surface tension or electrostatic adhesion of the liquid, the porous membrane is peeled off from the mount film with only the surface layer of the porous membrane remaining on the mount film.

[0102] According to the method for manufacturing a porous membrane described above, the flow rate of a fluid (liquid or gas) passing through the porous membrane can be improved (increased). Therefore, it is possible to achieve both a small pore size and an increased flow rate. Therefore, it is possible to manufacture a porous membrane with a small pore size and a large flow rate. In addition, the organic solvent (S2) (nitrogen-containing polar solvent having a boiling point of 200° C. or higher) remains in the porous membrane produced by the above-mentioned method for producing a porous membrane.

[0103] The porous membrane produced has an IPA flow rate of, for example, 0.21 mL / (min cm) as measured by the method described in [IPA flow rate (FR)] below. 2 ) or more and is 0.25mL / (min cm 2 ) or more. The produced porous membrane has a bubble point, measured by the method described in [Bubble Point (BP)] below, of, for example, 80 psi or more, and can also have a bubble point of 90 psi or more. The bubble point is an index of the pore size of the communicating pores, and the higher the bubble point, the smaller the pore size. The produced porous membrane has a tensile strength, measured by the method described in the below-mentioned section [Tensile strength], of, for example, 28 MPa or more, and can also be 30 MPa or more.

[0104] The porous membrane produced includes a structure in which spherical pores are interconnected (hereinafter, abbreviated as interconnected pores). The openings in the porous membrane are the portions where the interconnected pores open on the surface of the porous membrane.

[0105] The spherical shape of the hole includes a perfect sphere, but is not limited to a perfect sphere. The spherical shape may be substantially a perfect sphere, and includes a shape that can be recognized as a nearly perfect sphere when a magnified image of the hole is visually observed. Specifically, in the case of a spherical hole, the surface that defines the hole portion is a curved surface, and the curved surface may define a hole that is perfectly spherical or approximately perfectly spherical.

[0106] Individual spherical pores are typically formed by removing individual particles (B) present in the composite membrane (resin-particle composite membrane) in a subsequent particle removal step. Also, interconnected pores are formed in a porous membrane manufacturing method by removing multiple particles (B) present in contact with each other in the resin-particle composite membrane in a subsequent particle removal step. The locations at which the spherical pores interconnect are derived from the locations at which multiple particles (B) before removal contact each other.

[0107] The diameter of the openings in the porous membrane may be appropriately changed depending on the intended use of the porous membrane, for example, within the range of 100 nm or more and 5000 nm or less. The diameter of the opening is equal or approximately equal to the diameter of the spherical holes that make up the communicating holes. The communicating holes, which are formed by connecting spherical holes of such diameter, allow fluid to pass through the porous membrane well. The porous membrane has internal communicating holes that pass through the membrane in the thickness direction and serve as fluid flow paths, allowing the fluid to permeate from one main surface of the porous membrane to the other main surface. In addition, when the laminate is used as a filter, the fluid passes through the inside of the porous membrane while contacting the curved surface that defines each spherical pore. The contact area of ​​the fluid inside the porous membrane is quite large due to the presence of communicating pores consisting of spherical pores. Therefore, when the fluid passes through the laminate including the porous membrane, it is considered that minute substances present in the fluid are easily adsorbed by the spherical pores in the porous membrane.

[0108] ≪Porous membrane≫ The porous membrane contains at least one resin component selected from the group consisting of polyimide, polyamideimide, and polyethersulfone, and a nitrogen-containing polar organic solvent (S2) having a boiling point of 200° C. or higher under atmospheric pressure. The porous film is produced by a production method including forming a composite film made of the above-mentioned porous film production composition (varnish) on a substrate, heating the composite film to remove a part of the solvent (S) from the composite film, and removing the fine particles (B) from the heated composite film. That is, the porous film can be produced by the above-mentioned porous film production method. Since the porous membrane is manufactured using the above-mentioned composition (varnish) for manufacturing a porous membrane, the flow rate of the fluid passing through the porous membrane can be improved. Therefore, both the small pore size and the increased flow rate can be achieved. Therefore, a porous membrane with a small pore size and a large flow rate can be provided. EXAMPLES

[0109] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to the following examples.

[0110] [Examples 1-2 and Comparative Examples 1-2] A silica dispersion (containing 0.5% by mass of dispersant relative to silica) was added to the polyamic acid solution so that the amount of polyamic acid was 30% by mass and the amount of silica was 70% by mass relative to the total of the mass of polyamic acid (resin component (A)) and the mass of silica (fine particles (B)). Furthermore, as the solvent (S), organic solvent (1), organic solvent (2) and / or organic solvent (S') not corresponding to organic solvent (1) and organic solvent (2) were added so that the composition of the solvent (S) in the entire final composition (composition for producing a porous membrane (varnish)) was the mass % shown in Table 1. The resulting mixture was dispersed in a 1000 mL container by stirring with a stirring blade at 4000 rpm for 30 minutes. 2A dispersion process was carried out 10 times by passing the mixed liquid through the flow path at 200 MPa using a dispersion device equipped with a flow path of 1000 MPa, to prepare a composition for manufacturing a porous film (varnish) with a solid content concentration of 30 mass %. The ratio of polyamic acid to silica (polyamic acid:silica) in the obtained varnish was 38:62 in volume ratio and 30:70 in mass ratio. The following polyamic acid solution, organic solvent, dispersant, and fine particles were used. Polyamic acid solution: reaction product of pyromellitic dianhydride and 4,4'-diaminodiphenyl ether (solid content 20% by mass (organic solvent: N,N-dimethylacetamide)) Organic solvent (S1): N,N-dimethylacetamide (DMAc) Organic solvent (S2): N-methylpyrrolidone (NMP) or 1,3-dimethyl-2-imidazolidinone (DMI) · Organic solvent (S'): Gamma-butyrolactone (GBL) Dispersant: Polyoxyethylene secondary alkyl ether dispersant Fine particles (B): Silica with an average particle size of 100 nm

[0111] The obtained porous film manufacturing composition was applied to a polyethylene terephthalate (PET) film substrate using an applicator to form a composite film on the substrate (composite film formation step). Next, the composite film (unbaked composite film) was heated at 90°C for 5 minutes to remove a part of the solvent (S) (heating step). The composite film after the heating step was placed in an oven and baked at 380°C for 15 minutes to complete the imidization to obtain a resin-particle composite film (baking step). Then, this resin-particle composite film was peeled off from the substrate. The peeled resin-particle composite film was immersed in hydrogen fluoride (HF) for 10 minutes to remove the silica particles contained in the film (particle removal step). Then, it was washed with water and dried to obtain polyimide porous films of Examples 1-2 and Comparative Examples 1-2, each having a film thickness of 40 μm. Note that the organic solvent (S2) remained in the polyimide porous films of Examples 1 and 2.

[0112] The IPA flow rate (FR), bubble point (BP), and tensile strength of the obtained porous polyimide films of the Examples and Comparative Examples were measured according to the following methods. The results are shown in Table 1. [IPA Flow Rate (FR)] Each polyimide porous membrane was cut into a membrane filter size of 47 mm in diameter and attached to an in-line filter holder. Then, isopropyl alcohol (IPA) was pressurized with air at 0.1 MPa from the primary side (upstream side of the flow path of the porous membrane) to perform filtration, and the flow rate was measured. The measurement was carried out at 25°C. In Table 1, 2 It is expressed in mL per minute.

[0113] Bubble point The bubble point (BP) was measured in accordance with ASTM F316-86 and JIS K 3832. Specifically, each polyimide porous membrane was cut into a membrane filter size of 47 mm in diameter and attached to a measurement holder for bubble point. The secondary side of the membrane (the downstream side of the flow path of the porous membrane) was moistened with a fluorine-based solvent (Novec 7200, manufactured by 3M, hydrofluoroether), and air was gradually applied from the primary side to measure the pressure at which bubbles were generated on the secondary side. The measurement was performed at room temperature (25°C).

[0114] [Tensile strength] Each polyimide porous film was cut into a dumbbell-shaped No. 6 test piece to prepare a test piece. A small tabletop tester EZ Test EZ-SX (Shimadzu Corporation) was used as the tester, and the stress at break (tensile strength (MPa)) of the test piece was measured under the measurement conditions of 25°C and 5 mm / min in accordance with JIS K 7127.

[0115] [Table 1]

[0116] As shown in Table 1, Examples 1 and 2, which used a porous membrane production composition containing an organic solvent (organic solvent (S1)) having a boiling point of less than 200° C. under atmospheric pressure and a nitrogen-containing polar solvent (organic solvent (S2)) having a boiling point of 200° C. or higher under atmospheric pressure, had a flow rate 10% or higher than Comparative Example 1, which used a porous membrane production composition containing only the organic solvent (S1), and Comparative Example 2, which used a porous membrane production composition containing only the organic solvent (S1) and an organic solvent having a boiling point of 200° C. or higher but not a nitrogen-containing polar solvent. In particular, Example 1 had a higher flow rate than Example 2. In addition, Examples 1 to 2 and Comparative Examples 1 to 2 have the same bubble point (100 psi), and it can be said that the pore sizes are all small. Therefore, Examples 1 to 2 obtained porous membranes that achieved both small pore size and improved flow rate. In addition, Examples 1 to 2 also had higher membrane strength than Comparative Examples 1 to 2. In particular, Example 1 had higher membrane strength than Example 2.

Claims

1. The present invention comprises at least one resin component (A) selected from the group consisting of polyamic acid, polyimide, polyamideimide precursor, polyamideimide, and polyethersulfone, fine particles (B), and a solvent (S), The solvent (S) includes an organic solvent (S1) and an organic solvent (S2), The organic solvent (S1) has a boiling point of less than 200° C. under atmospheric pressure, The composition for producing a porous membrane, wherein the organic solvent (S2) is a nitrogen-containing polar solvent having a boiling point of 200° C. or higher under atmospheric pressure.

2. The composition for producing a porous membrane according to claim 1, wherein the nitrogen-containing polar solvent as the organic solvent (S2) is at least one selected from the group consisting of nitrogen-containing heterocyclic compounds which may have a substituent and aromatic hydrocarbons substituted with a nitrogen-containing group.

3. The composition for producing a porous membrane according to claim 2, wherein the organic solvent (S2) is at least one selected from the group consisting of 1,3-dimethyl-2-imidazolidinone, N-methylpyrrolidone, N-ethyl-2-pyrrolidone, and nitrobenzene.

4. The composition for producing a porous membrane according to claim 1 , wherein the organic solvent (S1) is an aliphatic amide-based solvent.

5. The composition for producing a porous membrane according to claim 4, wherein the organic solvent (S1) is dimethylacetamide.

6. 2. The composition for producing a porous membrane according to claim 1, wherein the ratio of the mass of the organic solvent (S2) to the mass of the solvent (S) is 5 mass% or more and 70 mass% or less.

7. 2. The composition for producing a porous membrane according to claim 1, wherein the content of the organic solvent (S2) is 100 parts by mass or more and 900 parts by mass or less per 100 parts by mass of the resin component (A).

8. A composite film forming step of forming a composite film made of the composition for producing a porous film according to any one of claims 1 to 7 on a substrate; a heating step of removing a portion of the solvent (S) from the composite membrane by heating the composite membrane; and a fine particle removing step of removing the fine particles (B) from the composite membrane after the heating step.

9. The resin component (A) contains at least one of a polyamic acid and a polyamide-imide precursor, The method for producing a porous film according to claim 8, further comprising a firing step of firing the composite film during the heating step or after the heating step and before the fine particle removing step.

10. A porous membrane comprising at least one resin component selected from the group consisting of polyimide, polyamideimide, and polyethersulfone, and a nitrogen-containing polar solvent having a boiling point of 200° C. or higher under atmospheric pressure, A porous film produced by a production method including: forming a composite film made of the composition for producing a porous film according to any one of claims 1 to 7 on a substrate; heating the composite film to remove a part of the solvent (S) from the composite film; and removing the fine particles (B) from the composite film after the heating.

Citation Information

Patent Citations

  • Transfer paper conveying device

    JP1981005566A